2019
DOI: 10.4103/ua.ua_59_18
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopy-free double-J stent placement through ureteroscope working channel postuncomplicated ureteroscopic laser lithotripsy: A novel technique

Abstract: Objectives:To report a technique for ureteroscopic laser lithotripsy (URSL) and retrograde placement of a double-J (DJ) stenting through the ureteroscope working channel without the use of a fluoroscope compared to the conventional technique.Patients and Methods:Between June 2015 and December 2017, 170 patients selected for URSL for treatment of ureteral stones and DJ insertion was evaluated. Patients are divided into two groups according to the use of fluoroscopy. In Group A (100 patients), fluoroscope is use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Stent composition and design have undergone many improvements but are still associated with morbidity in approximately 80% of cases [3]. Aboutaleb et al, reported DJS complications in 170 patients, with postoperative lower urinary tract irritative symptoms in the form of frequency and urgency in 63.5% patients, gross hematuria in 15.9% patients, and colic in 13.5% patients [1]. Upward migration of the stents was observed in 1.2% patients, while downward migration was observed in 5.9% patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stent composition and design have undergone many improvements but are still associated with morbidity in approximately 80% of cases [3]. Aboutaleb et al, reported DJS complications in 170 patients, with postoperative lower urinary tract irritative symptoms in the form of frequency and urgency in 63.5% patients, gross hematuria in 15.9% patients, and colic in 13.5% patients [1]. Upward migration of the stents was observed in 1.2% patients, while downward migration was observed in 5.9% patients.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, stent design and material have been upgraded to reduce complications. However, serious complications such as migration, fragmentation, encrustation, and stone formation may occur, especially when stents are left in respective locations for long periods [1]. In addition, a forgotten stent may be complex and challenging at the time of removal [2].…”
Section: Introductionmentioning
confidence: 99%
“…The Double J Stent, a self-retaining ureteral stent used for renal drainage, is widely used in urologic practice. It is used as a part of routine uretroscopy for stone disease, after a multitude of reconstructive surgeries to allow for uretral healing, for obstructive uropathy, before Extracorporeal Shock Wave Lithotripsy (ESWL), for obstructive anuria, etc [1]. However, serious complications such as encrustation, migration, stone formation, fragmentation, and infection can be seen if the stents have been placed for a long time [2].…”
Section: Introductionmentioning
confidence: 99%
“…Double J stents (DJS) are normally used in the treatment of obstructive anuria, ureteral reconstructive surgery, before extracorporeal shock-wave lithotripsy (SWL), and obstructive uropathy. 1 However, In addition, a forgotten stent may be complex and challenging at the time of removal . 2 Herein, we report a case of a forgotten DJS for 10 years that was complicated due to massive stone burden.…”
Section: Introductionmentioning
confidence: 99%